PENGARUH SOCIAL MEDIA OVERLOAD TERHADAP TECHNOSTRESS PADA SISWA: PERAN MEDIASI SELF-REGULATION - Diva Shakira Nuryadi; Henry Eryanto; Maulana Amirul Adha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Digital technology transformation has changed the learning process across various levels of education. The increasing use of social media as a manifestation of technological advancement has also given rise to technostress as a new challenge, making self-regulation is expected to play a crucial role as an internal capacity in managing these effects. This research was conducted to analyze the mediating role of self-regulation in the relationship between social media overload and technostress among students at SMKN 3 Jakarta. In this quantitative survey, the sample consisted of 118 Office Management students and was selected using the proportionate random sampling technique. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) based on the Partial Least Square (PLS) method in SmartPLS 4. The findings indicate that the direct effect of social media overload on technostress was not significant (β = -0,155; p = 0,147). In addition, social media overload on self-regulation (β = -0,309; p = 0,001) and self-regulation on technostress (β = -0,619; p < 0,001) both showed significant negative direct effects. Furthermore, self-regulation was found to fully mediate the relationship between social media overload and technostress (β = 0,191; p = 0,008). These findings indicate that self-regulation transmits the effect of social media overload on technostress, suggesting that the level of self-regulation is a determining factor in technostress levels.